Application of Germination and Combination Germination-Rhyzopus sp. treatment for Reduction of Ochratoxin A in Peanuts - Pratiwi, Amelinda; Dewi, Alifa Listina; Aisyah, Siti; Septiani, Widya Prasetyawati (Jurnal Kartika Kimia, 2025)
Peanuts are a major food commodity in Indonesia and an important source of protein, but their safety is compromised due to contamination by mycotoxins, including ochratoxin A (OTA). Several methods for OTA degradation have been explored, including chemical and physical approaches. However, biological methods like germination and a combination of germination with fungal treatment have shown potential for reducing OTA at a low cost. This study aimed to evaluate the effect of germination and a combined germination-fungal treatment using Rhyzopus sp. on the OTA content in peanuts. Peanuts spiked with 89.9 ppb OTA were subjected to germination for three days and the combination treatment. OTA degradation was analyzed using UHPLC-ESI-QQQ-MS/MS. The study found that germination and the germination-fungal treatment reduced OTA concentration on peanuts by 89.25% to 96.4%.